CCL5-armed oncolytic virus augments CCR5-engineered NK cell infiltration and antitumor efficiency. Issue 1 (24th February 2020) - Li, Feng; Sheng, Yuqiao; Hou, Weizhou; Sampath, Padma; Byrd, Daniel; Thorne, Stephen; Zhang, Yi
Abstract : Background: Natural killer (NK) cells have potent antitumor activities. Nevertheless, adoptive transfer therapy of NK cells has gained very limited success in patients with solid tumors as most infused NK cells remain circulating in the peripheral blood instead of entering tumor sites. Chemokines and their receptors play important roles in NK cell distribution. Enhancing chemokine receptors on immune cells to match and be driven to tumor-specific chemokines may improve the therapeutic efficacy of NK cells. Methods: The CCR5-CCL5 axis is critical in NK cell homing to tumor sites. Thus, we analyzed CCR5 expression on NK cells from patients with cancer and healthy donors. We then upregulated CCR5 and CCL5 with lentiviruses and oncolytic viruses in NK and tumor cells, respectively. Animal experiments were also carried out to test the efficacy of the combination of oncolytic virus with NK cells. Results: In NK cells from patients with various solid tumors or healthy subjects, CCR5 was expressed at low levels before and after expansion in vitro. CCR5-engineered NK cells showed enhanced tumor infiltration and antitumor effects, but no complete regressions were noted in the in vivo tumor models. To further improve therapeutic efficacy, we constructed CCL5-expressing oncolytic vaccinia virus. In vitro data demonstrated that vaccinia virus can produce CCL5 in tumor cells while infectivity remained unaffected. Supernatants from tumor cells infected by CCL5-modified vaccinia virus enhanced the directional movement of CCR5-overexpressed NK cells but not green fluorescent protein (GFP)-expressing cells. More importantly, NK cells were resistant to the vaccinia virus and their functions were not affected after being in contact. In vivo assays demonstrated that CCL5-expressing vaccinia virus induced a greater accumulation of NK cells within tumor lesions compared with that of the prototype virus. Conclusion: Enhancement of matched chemokines and chemokine receptors is a promising method of increasing NK cell homing and therapeutic effects. Oncolytic vaccinia viruses that express specific chemokines can synergistically augment the efficacies of NK cell-based therapy.